Intergenerational community conservation projects, STEM identity authoring, and positioning: the cases of two intergenerational teams. Issue 2 (3rd April 2021) - Campbell, Todd; Rodriguez, Laura; Moss, David M.; Volin, John C.; Arnold, Chester; Cisneros, Laura; Chadwick, Cary; Dickson, David; Rubenstein, Jesse M.; Abebe, Bethlehem
ABSTRACT: This research aimed to better understand the interaction between positioning and STEM identity authoring as intergenerational teams collaborated to complete community conservation projects, following a two-day conservation and geospatial technology workshop. Scientists and science educators supported these learners as they developed the focus, resources, timeline, and methods used to accomplish their negotiated pursuits at the two-day workshop and throughout their subsequent community project as a form of public engagement. To better understand the ways in which intergenerational teams located or positioned themselves and their partners, the ways in which teens and adults engaged in STEM identity authoring, and the interplay between positioning and STEM identity authoring a two-case study was completed. In this, field observations, interviews, and project artifacts were collected as the primary data sources. Findings emerging from the qualitative analysis of the data collected revealed how positioning and STEM identity authoring were found to be entangled and concurrently reinforcing even at the outset of the intergenerational teams' work. Additionally, positioning and STEM identity authoring in intergenerational teams were influenced by societal and cultural norms. These findings as well as recommendations emerging from the findings are further elaborated with the aim of supporting future intergenerational work of teens and adults in informal STEM learning contexts.